Panel: Getting Global With It: Youth Global Participation in the Digital Age - Plutte, Chris; Rubio, Juan; Cervone, Barbara; Inkpen, Kori; Hinton, Christina; Moorman, Honor (2013)
With an internationally interdependent economy, unprecedented migration, and information continuously circulating the planet, children are growing up in a globalized world. In this 21st century world, children need to learn about international issues, develop intercultural understanding, and participate in the global society. Modern digital technologies provide new avenues for helping children gain these critical skills. At the click of a button, children in different countries can have a virtual playdate, collaborate on a project, or share media about their cultures. This panel brings together experts from technology companies, international NGOs, and nonprofits to discuss innovative initiatives that use technology to help children ages 7 – 11 learn about international issues, connect across cultures, and participate in the global society.
Digital Media and Learning Conference 2013